Meningkatkan Pemahaman Konsep Matematika Siswa Sekolah Dasar Dalam Operasi Bilangan Bulat Menggunakan Media Koin Bermuatan - Gisca Zalfa Hansa; Ibnu Muthi (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
The low results of daily tests on mathematics subjects regarding integer arithmetic operations indicate a lack of mastery of the material. This research aims to increase elementary school students' understanding of integer counting operations through the use of charged coins. Charged coin media uses capsule coins with positive and negative charges attached to cardboard, which is designed to help students understand the concept of integer counting operations. The research method used is a literature review where researchers use journals contained in GoogleSchool which were published in 2015-2023. Based on this research, the results showed that the use of charged coin media is very appropriate for increasing students' understanding of mathematical concepts in whole number operations.